The Emerging Roles of the Science Teacher in School Health in Light of the Corona Covid- 19 Crisis from the Point of View of Teachers of the Northeastern Badia - ALSHARAFAT, SAYAR SAYAH SALEM (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the emerging roles of the science teacher in school health in light of the Corona crisis from the point of view of teachers of the northeastern Badia, using the descriptive survey method, through a questionnaire that consisted of (20) items, and its sample consisted of (100) teachers who were chosen by the simple random method from School teachers in Badia Governorate, and the results showed that the estimates of the emerging roles of the science teacher in school health in light of the Corona crisis from the point of view of the teachers of the northeastern Badia came with a high degree of appreciation with an arithmetic mean of (3.86), as for the fields, the arithmetic averages ranged between ( 3.81- 3.92), where the follow- up field came in the first place with the highest arithmetic mean of (3.92), while the field of prevention came in the last rank with a mean of (3.81). The results also showed that there were no statistically significant differences (a = 0.05) due to the effect of The scientific qualification in all fields and in the total degree of the tool, and in light of the results, several recommendations were made, the most important of which is urging the Ministry of Education to conduct more training courses and workshops to clarify the importance of school health in facing the spread of the Corona virus.
Keywords: Emerging Roles; Science Teacher; School Health; "Covid- 19" Crisis